2009
DOI: 10.1176/ps.2009.60.11.1489
|View full text |Cite
|
Sign up to set email alerts
|

Health Services Determinants of the Duration of Untreated Psychosis Among African-American First-Episode Patients

Abstract: Objective The duration of untreated psychosis is associated with poor outcomes in multiple domains in the early course of nonaffective psychotic disorders, although relatively little is known about determinants of this critical period, particularly health services–level determinants. This study examined three hypothesized predictors of duration of untreated psychosis (lack of insurance, financial problems, and broader barriers) among urban, socioeconomically disadvantaged African Americans, while controlling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…In fact, aside from our own studies, we are unaware of other research that focuses on this population. In our prior independent sample, we found that DUP is predicted by mode of onset of psychosis, living below the federal poverty level, poor family functioning, not having health insurance, the family’s report of financial problems, and the family’s report of barriers to seeking care (Compton et al, 2009a; Compton et al, 2009b; Compton et al, 2011). In the present study, we extend this line of research by studying additional hypothesized predictors of treatment delay in another sample comprised predominantly of African Americans.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In fact, aside from our own studies, we are unaware of other research that focuses on this population. In our prior independent sample, we found that DUP is predicted by mode of onset of psychosis, living below the federal poverty level, poor family functioning, not having health insurance, the family’s report of financial problems, and the family’s report of barriers to seeking care (Compton et al, 2009a; Compton et al, 2009b; Compton et al, 2011). In the present study, we extend this line of research by studying additional hypothesized predictors of treatment delay in another sample comprised predominantly of African Americans.…”
Section: Introductionmentioning
confidence: 89%
“…A rating of “3-recurrent” is defined as “has had the symptom at least half of the time and the symptom has persisted at least three consecutive months. A rating of “4-continuous” is given when the person “has had the symptom everyday or almost everyday continuously up to the initial treatment contact.” Prior reports describe our standardized approach to using the SOS and deriving age at onset and DUP using consensus-based best-estimate methods (Compton et al, 2008a; Compton et al, 2009a; Compton et al, 2009b; Compton et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also conducted a similar in-depth interview with one or two family members/informants when available. Then, we derived consensus-based best estimates of age at onset of the prodrome and age at onset of psychosis in a standardized fashion, using all available information, as described in prior reports (Compton et al, 2008, Compton et al, 2009a, Compton et al, 2009c, Compton et al, 2011, Compton et al, 2012, Broussard et al, 2013). Dates, including a minimum of month and year, of age at onset of these symptoms were recorded, allowing these variables to be coded in months rather than years.…”
Section: Methodsmentioning
confidence: 99%
“…Being uninsured predicts delayed help seeking following onset of psychosis (6) as well as less use of community mental health treatment and greater likelihood of using only crisis or emergency services (7). In the Suffolk County (New York) Mental Health Project, 44% of patients with a first admission for psychosis were uninsured (8).…”
mentioning
confidence: 99%